The Effect of Social Skill Therapy on Internet Addiction of Undergraduates in a Nigerian University - Omoyemiju, Michael Adeniyi (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The efficacy of social skill therapy (SST) for ameliorating internet addiction was tested among young Obafemi Awolowo University students. A total of 1,448 students were selected to participate in the study. The Internet Addiction Test was employed in the collection of data. The data collected were analyzed using percentages and analysis of covariance. A significant effect of SST [F (1, 59) = 82.243, p < 0.05] on Internet addiction was found. The study concluded that SST was an effective therapy for ameliorating Internet addiction among students.